Clinical significance of PET/CT uptake for peripheral clinical N0 non‐small cell lung cancer. (13th February 2020) - Wang, Shuai; Lin, Dong; Yang, Xiaodong; Zhan, Cheng; Zhao, Shihai; Luo, Rongkui; Wang, Qun; Tan, Lijie
Abstract: Objective: In this cohort study, we determined the clinical value of the maximum standardized uptake value (SUVmax) of primary tumors in non‐small cell lung cancer (NSCLC). Study Design: A retrospective review of NSCLC patients was performed from January 2011 to December 2017. Peripheral cN0 NSCLC patients with tumor size ≤2 cm were included. SUVmax was calculated as a continuous variable for semiquantitative analyses. A receiver operating characteristic curve was analyzed to assess the cutoff threshold of SUVmax on pathological (p) nodal metastasis. We further evaluated the clinical relevance of SUVmax in peripheral cN0 NSCLC patients. Results: A total of 670 peripheral NSCLC patients with tumor size ≤2 cm were deemed cN0 by preoperative PET/CT scan. Statistical analyses suggested significant correlations of SUVmax with smoking status ( P  = .026), tumor volume ( P  = .001), pathology type ( P  = .008), tumor differentiation ( P  < .001), vessel invasion ( P  = .001), plural invasion ( P  < .001), pT stage ( P  < .001), nodal involvement ( P  < .001), and pathological tumor node metastasis stage ( P  < .001). A cutoff point of SUVmax of 3.8 ( P  < .001) could be used to predict pathological nodal metastasis. Multivariable analyses indicated that preoperative SUVmax >3.8 (odds ratio, 12.149; P  < .001) was an independent predictor of nodal metastasis. Overall survival analyses further suggested that SUVmax was an independent prognostic indicator (hazard ratio, 2.050; P  = .017). Conclusion: Preoperative SUVmax is a predictor of pathological nodal metastasis and prognosis for peripheral cN0 NSCLC patients with tumor size ≤2 cm. Our results indicate that assessment of PET SUVmax could improve stratification of these patients. Abstract : Preoperative SUVmax of primary lesions is a predictor of pathological nodal metastases in peripheral cN0 NSCLC with tumor size ≤2 cm. Primary tumor SUVmax is associated with key clinicopathological features and prognosis of patients with peripheral cN0 NSCLC with tumor size ≤2 cm.